2020
DOI: 10.3390/nu12010179
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Low GI Diet on Truncal Fat Mass and Glycated Hemoglobin in South Indians with Type 2 Diabetes—A Single Centre Randomized Prospective Study

Abstract: Background: There has been no previous study that has investigated the effect of a low glycemic index (LGI) diet with local recipes of South Indian cuisine on the body fat composition using dual-energy X-ray absorptiometry (DXA). Truncal obesity has been associated with the risk of metabolic disorders and cardiovascular diseases. Aim: The aim of this study was to examine the effect of a low GI diet on glycemic control and body composition in people with type 2 diabetes in South India. Method: This was a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…The present systematic review and meta-analysis show that an LGID is superior to a number of other diets in the control of body mass, which is consistent with the results of previous studies [15,32,40,43,47]. Furthermore, stratified analyses of the duration of the intervention showed that studies with a duration of ≥24 weeks generated more consistent results and larger reductions in body mass and BMI.…”
Section: Discussionsupporting
confidence: 91%
“…The present systematic review and meta-analysis show that an LGID is superior to a number of other diets in the control of body mass, which is consistent with the results of previous studies [15,32,40,43,47]. Furthermore, stratified analyses of the duration of the intervention showed that studies with a duration of ≥24 weeks generated more consistent results and larger reductions in body mass and BMI.…”
Section: Discussionsupporting
confidence: 91%
“…These benefits are recognised by major international clinical practice guidelines in Canada, USA, Australia, UK, and Europe,117181920 with low GI/GL dietary patterns recommended for those with diabetes. Despite this recognition, the European Association for the Study of Diabetes (EASD) last updated their clinical practice guidelines in 200418 and the last comprehensive systematic review and meta-analysis in diabetes was published in 2010,78 with numerous randomised controlled trials published after the census for these syntheses 2122232425262728293031. To inform the update of EASD clinical practice guidelines for nutrition treatment, the Diabetes and Nutrition Study Group (DNSG) of EASD commissioned a systematic review and meta-analysis of randomised controlled trials to summarise the effect of low GI/GL dietary patterns on glycaemic control and other established cardiometabolic risk factors in people with type 1 and type 2 diabetes and assess the certainty of the evidence using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach.…”
Section: Introductionmentioning
confidence: 99%
“…From a scientific perspective, the GI has been successfully used as part of a diet-based approach to manage blood glucose levels in individuals with diabetes [ 86 , 87 , 88 , 89 , 90 , 91 ]. Guidelines for the management of diabetes in Canada, Australia, Europe, the UK, and the US acknowledge that low GI dietary patterns can be used to assist with blood glucose management [ 92 , 93 , 94 , 95 ].…”
Section: Labelling Foods For Carbohydrate Qualitymentioning
confidence: 99%